1999
DOI: 10.1002/(sici)1521-3838(199901)18:1<43::aid-qsar43>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Activity and Structure–Toxicity Relationships of 4‐Aminodiphenyl Sulphone Derivatives with Antiinflammatory Activity

Abstract: It has been shown that dapsone and its derivatives are not only potential inhibitors of bacterial and plasmodial folate synthesis but also possess antiin¯ammatory activity. The application of dapsone is, however, limited by its toxic side effects at higher dose manifested especially by its potential to produce methaemoglobin. We have analyzed the structural dependence of this property on a set of 29 derivatives. A highly signi®cant nonlinear dependence on the lipophilicity could be derived. Two exceptions to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Wachall et al, 350 in the study of imidazole-substituted biphenyls, potential agents for the treatment of prostate cancer, obtained correlations between biological activity and TLC retention coefficient, R M , determined on octadecylbonded silica plates. Seydel et al 351 studied the toxicity of 4-aminodiphenylsulfone derivatives used in the therapy of bacterial infections, malaria, and toxoplasmosis. It was found that methemoglobin production, reflecting compounds toxicity, significantly correlated with lipophilicity parameters determined chromatographically.…”
Section: Quantitative Structure−enantioselective Retention Relationsh...mentioning
confidence: 99%
“…Wachall et al, 350 in the study of imidazole-substituted biphenyls, potential agents for the treatment of prostate cancer, obtained correlations between biological activity and TLC retention coefficient, R M , determined on octadecylbonded silica plates. Seydel et al 351 studied the toxicity of 4-aminodiphenylsulfone derivatives used in the therapy of bacterial infections, malaria, and toxoplasmosis. It was found that methemoglobin production, reflecting compounds toxicity, significantly correlated with lipophilicity parameters determined chromatographically.…”
Section: Quantitative Structure−enantioselective Retention Relationsh...mentioning
confidence: 99%
“…O exemplo mais notável é aquele mostrado pelas sulfas, que descrevem a potência através de um coeficiente negativo para a partição 16,18,19 . Seydel e colaboradores, no entanto, encontraram outro exemplo no caso de hidrazidas do ácido nicotínico atuando frente a M. tuberculosis.…”
Section: Resultsunclassified
“…Principal component analysis (PCA) as a versatile and easy to carry out multivariate method has been frequently employed for the elucidation of the relationship between biological activity and molecular characteristics [6]. PCA has been successfully used for improving ligand selectivity in receptor-based drug design [7], for the study of the substituent effects of meta and para benzene derivatives [8], for the characterization of amino acids [9], for the evaluation of aquatic toxicity of xenobiotics [10], and for the study of the structure-activity and structure-toxicity relationships of anti in¯ammatory drugs [11]. PCA forms clusters of variables and observations taking into consideration simultaneously the strength and selectivity of the biological effect under investigation that is PCA cannot be employed when the separation of the strength and selectivity of the effect is required.…”
Section: Introductionmentioning
confidence: 99%